La fragmentación del cuerpo femenino y la degradación del yo lírico a partir de la escritura femenina en La Mano Suicida - Araya Jiménez, Xinia (2014)
This article analyzes the work of Maria Montero entitled La mano suicida, which shows the formation of the female lyric writing from the fragmentation of the female body and its degradation as a subject writer. It takes into consideration the classification attributed by Francisco Rodriguez Cascante (2006) on Costa Rican contemporary poetry, in which she argues that the work of Montero responds to individualistic poetry. Similarly, literary creation will be considered as the means of communication used by the lyrical first to bring out it’s social unrest.